Impact of window design on the lighting environment of GAP-certified naturally illuminated broiler houses - Joshua A. Etherton; John E. Linhoss; Jeremiah D. Davis; Joseph L. Purswell; Jessica D. Starkey (PLoS ONE, 2025)
Recent changes in consumers’ desire for alternative rearing programs have prompted integrators to adopt varying fenestration designs in commercial broiler houses, most notably the inclusion of natural light (NL) via windows. The objectives of this study were to compare light intensity, spatial distribution, and uniformity in two 18.2 × 182.9 m commercial broiler houses in southeast Alabama with different window designs. Window designs in both houses met Global Animal Partnership (GAP) NL standards. The one-sided window (1SW) design had 23 translucent windows (1.42 × 1.09 m) that were all located on the north wall. The two-sided window (2SW) design had 58 translucent windows (0.95 × 0.60 m) located on both the north and south sidewalls and two additional windows of the same size on the west end wall (brooding end). Data acquisition systems were constructed to collect floor light intensity at 750 locations per replicate in both houses. Two replicates were collected for tunnel and brooding conditions in each house at solar noon ± 1 h. Mean light intensity in three house sections (fan, mid, and pad) were compared as well as whole house data for both tunnel and brood conditions. The GSTAT package in R was used to spatially map light intensities. During tunnel ventilation conditions, mean light intensity values were 1.8 times and 6.5 times higher in the mid and pad sections, respectively, in the 2SW design than the 1SW design. Light intensities during brood conditions were similar between designs (1SW = 44.7 lx; 2SW = 43.7 lx) due to the masking effect of the brighter artificial lighting targets (brooding = 43 lx; tunnel = 1 lx). Coefficients of variation (CV) were higher in the 1SW than the 2SW during brooding [63.7% (1SW) vs 56.4% (2SW)] and tunnel [192.2% (1SW) vs 143.9% (2SW)], indicating reduced spatial uniformity in the 1SW house. This study showed that the 2SW design can lead to higher overall intensities and improved spatial uniformity during tunnel conditions. Results from this study could help inform future window designs in commercial broiler houses.